GERMANIUM ISOTOPIC COMPOSITIONS IN CANYON DIABLO SPHEROIDS - Xue S.; Yang Y.L.; Hall G.S.; Herzog G.F. (My University, 1997)
By using ICP-MS, we have measured the concentrations and isotopic abundances of Ge in the following samples: (1) the iron meteorites Camp Verde, Toluca, Picacho, and Canyon Diablo; (2) Canyon Diablo spheroids; and (3) oxide rims and metallic cores obtained by grinding Canyon Diablo spheroids. Whole Canyon Diablo spheroids contain appreciably more Ge than does the bulk meteorite. Germanium is enriched in the metallic cores of the spheroids where concentrations may exceed 500 ppm. It is depleted in the oxide rims compared to the metallic cores and to the bulk meteorite. The major isotope ratios, 72Ge/70Ge, 73Ge/70Ge, and 74Ge/70Ge, were determined with an uncertainty of ~0.3% (1σ). The isotopic abundances of Ge in the bulk iron meteorites and the metallic cores of spheroids match terrestrial values. However, the oxide rims of spheroids contain mass-fractionated Ge (4 +/- 1%%/AMU), providing the first direct evidence for evaporative loss from these objects. Assuming Rayleigh distillation and GeO as the evaporating species, we estimate that about 50% of the Ge in the precursor of the oxide rims remains there.